ANALISIS KUALITAS PELAYANAN PELANGGAN BARU OLEH PDAM TIRTA AGUNG KABUPATEN TEMANGGUNG - Imam Setyo Nugroho; Zaenal Hidayat; Hartuti Purnaweni (Journal of Public Policy and Management Review, 2013)
This paper aims to determine the quality implementation of new customer service on PDAM Tirta Agung Temanggung RegencyTheoretically PDAM Tirta Agung Temanggung Regency has adopted the concept of good service to new customers that provide services forcing registrations and new connections.In real terms the services provided by PDAM Tirta Agung Temanggung Regency for a new customer is still not optimal, there are some issues such as timeliness of service, and installation costs are not equal among customers for several reasons. Recommendations from this research is that in order to improve the quality of customer service new PDAM Tirta Agung Temanggung regency, then a few things such as target setting within easy reach, increase on-time service, as well as the determination of costs associated services need to be done with the new customer service activities.